TIPOLOGI KOMENTAR PENGUNJUNG PADA DAERAH WISATA LOVINA DI SITUS PARIWISATA TRIP ADVISOR - Kadek Wiramarta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Currently, one of the internet platforms that is most often used as consideration in making travel decisions is Trip Advisor. In Trip Advisor, visitors will be helped to make right decision while traveling based on information from tourist attractions and reviews from previous visitors. On the other hand, Lovina, as one of the main tourist attractions in Singaraja, cannot be separated from this Trip Advisor site. As a tourist area that is developing, Lovina must continue to improve and the Trip Advisor site can be used as a basis for this improvement. Based on the above problems, the author would like to study about the positive and negative revies from visitors regarding Lovina Beach. A literature study was made based on visitors’ comments or reviews of Lovina Beach on the Trip Advisor site in the last 5 year (2014 - 2018). The results of the literature study are as follows. Positive comments that arise about Lovina beach are on the attractions of interesting dolphin tours, the soothing atmosphere of Lovina, tourist accommodation such as satisfying hotels and restaurants, experienced tour guides and incredible sunset attractions. Of the many complaints, it can be mapped that tourists 'dissatisfaction with Lovina tends to be in dolphin tourism attractions that sacrifice dolphins' life in the wilderness, dirty beach and seawater, street traders and vendors who force their stuffs, security, lack of tourist attractions, unsuitable atmosphere with tourist expectations and distant location from other tourism object. Keywords: Lovina, Reviews, Typology, Trip Advisor